2004
DOI: 10.1002/art.20037
|View full text |Cite
|
Sign up to set email alerts
|

Novel tumor necrosis factor α–regulated genes in rheumatoid arthritis

Abstract: Objective. To determine novel genes regulated by tumor necrosis factor ␣ (TNF␣) signaling in primary rheumatoid arthritis synovial fibroblasts (RASFs).Methods. Oligonucleotide microarrays were used to measure gene expression levels in 6 independent replicate samples of RASFs. RASFs were transfected for 18 hours with AdIB-dominant negative (AdIB-DN) (n ‫؍‬ 3) or with control AdTet expressing the reverse tetracycline trans-activator (n ‫؍‬ 3). The cells were stimulated for 3 hours with TNF␣, and total RNA was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 50 publications
1
62
0
2
Order By: Relevance
“…We also have demonstrated that these fibroblasts exhibit abnormal up-regulation of numerous genes, including cytokines, chemokines, inflammation mediators, and members of the TNF superfamily of receptors, including RANKL (18). Other investigators have observed that survival genes, such as FLIP and SUMO-1, are expressed by synovial fibroblasts (33,34).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…We also have demonstrated that these fibroblasts exhibit abnormal up-regulation of numerous genes, including cytokines, chemokines, inflammation mediators, and members of the TNF superfamily of receptors, including RANKL (18). Other investigators have observed that survival genes, such as FLIP and SUMO-1, are expressed by synovial fibroblasts (33,34).…”
Section: Discussionmentioning
confidence: 68%
“…The close association of the macrophages and MSFs, together with the abnormal osteoclast formation at the sites of bone erosion, suggests that the fibroblastmacrophage interaction may lead to osteoclast formation. To determine whether the spontaneous erosion and osteoclast formation in BXD2 mice is due to either an abnormal MSF phenotype, an abnormal macrophage phenotype, or both, MSFs were derived from BXD2 mice as well as B6 and D2 mice, as described previously (18). After 7 days of culture, primary cultures of MSFs were established, as indicated by the expression of vimentin ( Figure 3A), an intermediate filament that is expressed in fibroblasts but not macrophages (19).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More relevant to RA disease in particular was the attempt to generate a molecular profile of synovial tissue from RA patients using primary synovial fibroblasts (38,50). The analysis of gene expression patterns of primary as well as cultured synovial fibroblasts revealed the involvement of the TNF-␣ pathway in the pathogenesis of RA (24,79). Array-based approaches in synovial tissues, being the key target of the disease, showed lower variation of gene expres-sion differences in different synovial biopsies from the same patient compared with those of different patients (46).…”
mentioning
confidence: 99%
“…Accordingly, we performed experiments at two time points (1.5 and 3 h after receptor-specific cross-linking) to screen for genes differentially regulated by the WT and TL receptors. To identify target genes putatively regulated by the CY of Fc␥RIa ␣-chain, we analyzed the hybridization data to identify genes with a hybridization signal with Ն2-fold difference in signal intensity between the WT and TL cell lines in three independent experiments and with a statistically significant differences (regular t test with a Bonferroni correction; p Ͻ 0.05) as described (22). Based on these criteria, we identified five genes which are immunologically related to the functions of macrophages (Table II).…”
Section: Microarray Analysis Of Differential Gene Expression Induced mentioning
confidence: 99%